MENGINISIASI DIPLOMATIC GOVERNANCE DALAM PERUMUSAN DAN ARTIKULASI POLITIK LUAR NEGERI - Herningtyas, Ratih (JPP (Jurnal Politik Profetik), 2015)
This paper tries to discuss diplomatic governance study on Indonesian decision-making and implementing foreign policy. Diplomatic governance is a concept that is adopted from democratic study on how to manage transparent and accountable decison-making policy. The discourse on diplomatic governance is expected to improve effectivity and efficiency of Indonesian foreign policy in achieving its national interests. Foreign policy that will be the focus of this paper is Indonesiaan foreign policy of administrative–based economy. In the last 10 years, this policy have been constractedserious problems such as corruption, lack of protection of Indonesian citizen abroad and crisis on law-politics issues such as dispute resolution in International Court of Justice in the case of Sipadan and Ligitan Islands.This paper considers that the lacks of effective and efficient of Indonesian foreign policy in articulating Indonesia‟s national interests in international fora are closely related to the low governance negotiation discourse in the formulation and implementation of Indonesia's foreign policy.